2003
DOI: 10.1046/j.1095-8339.2003.t01-1-00158.x
|View full text |Cite
|
Sign up to set email alerts
|

An update of the Angiosperm Phylogeny Group classification for the orders and families of flowering plants: APG II

Abstract: A revised and updated classification for the families of the flowering plants is provided. Newly adopted orders include Austrobaileyales, Canellales, Gunnerales, Crossosomatales and Celastrales. Pertinent literature published since the first APG classification is included, such that many additional families are now placed in the phylogenetic scheme. Among these are Hydnoraceae (Piperales), Nartheciaceae (Dioscoreales), Corsiaceae (Liliales), Triuridaceae (Pandanales), Hanguanaceae (Commelinales), Bromeliacae, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
0
9

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 2,309 publications
(143 citation statements)
references
References 96 publications
6
105
0
9
Order By: Relevance
“…Ximenia (Ximeniaceae) pollen shows the same general morphological features than the reticulate pollen seen in most Strombosiaceae and Erythropalaceae (Maguire et al 1974; Feuer 1977). That the same basic pollen type is shared by various early diverging lineages of the Santalales (formerly included in the ‘Olacaceae s.l .’ grade; Feuer 1977; APG 2003) indicates that the 3-colpate, triangular bipyramidal-spheroidal pollen grains with psilate-perforate to reticulate sculpturing represent the most primitive pollen type of the Santalales. This primitive type has been conserved in these early diverging lineages (primary divergences have been dated to c .…”
Section: Discussionmentioning
confidence: 99%
“…Ximenia (Ximeniaceae) pollen shows the same general morphological features than the reticulate pollen seen in most Strombosiaceae and Erythropalaceae (Maguire et al 1974; Feuer 1977). That the same basic pollen type is shared by various early diverging lineages of the Santalales (formerly included in the ‘Olacaceae s.l .’ grade; Feuer 1977; APG 2003) indicates that the 3-colpate, triangular bipyramidal-spheroidal pollen grains with psilate-perforate to reticulate sculpturing represent the most primitive pollen type of the Santalales. This primitive type has been conserved in these early diverging lineages (primary divergences have been dated to c .…”
Section: Discussionmentioning
confidence: 99%
“…54 genera and 2,600 species (including Cecropiaceae) (APG II 2003, APG III 2009 and is widely distributed from tropical to temperate regions with a centre of diversity in tropical Asia. Most Urticaceae species have minute unisexual flowers with a reduced perianth, which makes hypotheses of morphological homology very difficult (Monro 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular data and floral structure showed that Anisophylleaceae are closest to the Cucurbitales (Setoguchi et al 1999, Schwarzbach & Ricklefs 2000, Matthews et al 2001, Zhang et al 2006, 2007, Schaefer & Renner 2011 and modern classifications accept the family as a member of the Cucurbitales (Angiosperm Phylogeny Group 1998Group , 2003Group , 2009). …”
Section: Affinities Of Anisophylleaceae With Other Familiesmentioning
confidence: 99%